2010
DOI: 10.1063/1.3309745
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen vacancies on relaxation and conduction behavior of KNbO3 ceramic

Abstract: The temperature and frequency dependent dielectric and conductivity properties were measured on as-sintered as well as oxygen annealed KNbO3 ceramics. The results show that in addition to phase transition peaks, well defined relaxation peaks are observed in the temperature range 450–700 K. These peaks could be suppressed by annealing the samples in the oxygen atmosphere. The dc conductivity and maximum dielectric constant values decreases after oxygen annealing. Activation energy, calculated from dielectric re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 56 publications
5
56
0
Order By: Relevance
“…It is much smaller than the typical activation energy (~1000 meV) of ions, oxygen vacancies and/or dipoles in oxides. For instance, the activation energy of oxygen vacancies is 910 meV for BaTiO 3 22 , 1005–1560 meV for KNbO 3 30 , and 1030 meV for YBCO ceramics 31 . Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…It is much smaller than the typical activation energy (~1000 meV) of ions, oxygen vacancies and/or dipoles in oxides. For instance, the activation energy of oxygen vacancies is 910 meV for BaTiO 3 22 , 1005–1560 meV for KNbO 3 30 , and 1030 meV for YBCO ceramics 31 . Liu et al .…”
Section: Resultsmentioning
confidence: 99%
“…29 It has been reported that the defects such as A-site vacancies, space charge electrons, 26 oxygen vacancies, 27 or other impurities are responsible for the dielectric relaxation in high temperature region.…”
Section: Resultsmentioning
confidence: 99%
“…Generally speaking dielectric relaxation due to interfacial polarization, space charge, domain wall motion, Maxwell-Wagner polarization, defect relaxation, and long-range structure disorder usually occurs at low frequency region, however, dipolar relaxation appears at higher frequency. 29,30 It is widely accepted that dielectric relaxation in dielectric materials in the temperature region above room temperature is usually related to OVs, and the hopping motions of singly/doubly-ionized OVs can lead to a relaxation processes in low-frequency region typically below mega hertz. 30,31 Thus, we consider that the relaxation observed in lower frequency spectrum should belong to space charge which may be due to oxygen vacancy and related defects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dielectric constant and dielectric loss increased with decreasing frequency, indicating high permittivity at low frequency is related to conductive properties. Dielectric relaxation observed in low frequency is attributed to space charges such as oxygen vacancies [6,7]. Thus the substitution of Mn 4+ decreases space charges while the substitution of Mn 2+ and Mn 3+ increases space charges [8].…”
Section: Methodsmentioning
confidence: 96%